Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.24017/science.2020.ichms2020.4
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s Information Toward Some Modifiable Risk Factors of Ischemic Heart Disease

Abstract: Ischemic heart disease (IHD), , is the condition of heart problems, caused by narrowed coronary arteries that supply oxygenated blood to the heart muscle. There is a shortage of study of bachelor students. The goal of this research was directed to assess level of patient’s information toward some modifiable risk factors of IHD at Rania teaching hospital in Kurdistan region of Iraq during the period of (20th October 2019 - 10th February 2020). A non- probability purposive sample of (143) patients; the study ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…al. [14], who indicated that nearly almost of their participants did not eat healthy food daily such as Plenty of fruits and vegetables, foods low in saturated fat, cholesterol, salt, sugar and high in fiber. The researcher believed that these participants had sufficient information about heart disease and it is risk factors but they did not practice their information in their daily life, which is the disaster.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [14], who indicated that nearly almost of their participants did not eat healthy food daily such as Plenty of fruits and vegetables, foods low in saturated fat, cholesterol, salt, sugar and high in fiber. The researcher believed that these participants had sufficient information about heart disease and it is risk factors but they did not practice their information in their daily life, which is the disaster.…”
Section: Discussionmentioning
confidence: 99%
“…al. [14] who mentioned that more than half of their participants had information about ischemic heart disease but agree in the source of their information because the highest proportion of their source of information was the physicians. There were no participants had any information about food-drug interaction and drug-drug interaction.…”
Section: International Journal Ofmentioning
confidence: 99%
“…The researchers believe that this condition is related to lack of nursing home care, health awareness, and absence of teamwork among different specialists in a special centre for rehabilitation and copying heart failure patients with this difficult situation; because of this, the cardiologist and cardiologist nurses in the coronary care unit should scientifically behave with heart failure patients to decrease the level of patients' stress, because the nurse plays a vigorous role in discovering and assisting with the discomfort of patient regularly; that is the reason it is significant for attendants to put on clinical rules into attention the heart disease patient to reduce their suffering. Professional or expert nurses accept a massive job in diminishing the worldwide weight and taking an interest in improving the outcome of the individual and networks, so the nurses also need knowledge, awareness, and practices that will assess them to function as contributors in a multidisciplinary group in resolving heart disease (11,12) . Therefore, the finding of this study recommended that the Ministry of health start working with teamwork among cardiologist nurses, cardiologists, psychiatrists, clinical psychologists, pharmacists, nutritionists, neurologists, and patient's families or caregivers to assess heart failure patients to adapt to this difficult condition and to decrease the level of stress.…”
Section: Discussionmentioning
confidence: 99%